Targeting the Interplay Between Cancer Fibroblasts, Mesenchymal Stem Cells, and Cancer Stem Cells in Desmoplastic Cancers - Chan, Tze-Sian; Shaked, Yuval; Tsai, Kelvin K. (Frontiers in Oncology, 2019)
Malignant tumors are highly heterogeneous and likely contain a subset of cancer cells termed cancer stem cells (CSCs). CSCs exist in a dynamic equilibrium with their microenvironments and the CSC phenotype is tightly regulated by both cell-intrinsic and cell-extrinsic factors including those derived from their surrounding cells or stroma. Many human solid tumors like breast, lung, colorectal and pancreatic cancers are characterized by a pronounced stromal reaction termed “the desmoplastic response”. Carcinoma-associated fibroblasts (CAFs) derived either from resident fibroblasts or tumor-infiltrating mesenchymal stem cells (MSCs) are a major component of the stroma in desmoplastic cancers. Recent studies identified subpopulations of CAFs proficient in secreting a plethora of factors to foster CSCs, tumor growth and invasion. In addition, cytotoxic therapy can lead to the enrichment of functionally perturbed CAFs, which are endowed with additional capabilities to enhance cancer stemness, leading to treatment resistance and tumor aggressiveness. When recruited into the tumor stroma, bone-marrow-derived MSCs can promote cancer stemness by secreting a specific set of paracrine factors or converting into pro-stemness CAFs. Thus, blockade of the crosstalk of pro-stemness CAFs and MSCs with CSCs may provide a new avenue to improving the therapeutic outcome of desmoplastic tumors. This up-to-date, in-depth and balanced review describes the recent progress in understanding the pro-stemness roles of CAFs and tumor-infiltrating MSCs and the associated paracrine signaling processes. We emphasize the effects of systemic chemotherapy on the CAF/MSC_CSC interplay. We summarize various promising and novel approaches in mitigating the stimulatory effect of CAFs or MSCs on CSCs that have shown efficacies in preclinical models of desmoplastic tumors and highlight the unique advantages of CAF- or MSC-targeted therapies. We also discuss potential challenges in the clinical development of CSC- or MSC-targeted therapies and propose CAF-related biomarkers that can guide the next-generation clinical studies.